FOSTERING ORGANIZATIONAL CITIZENSHIP BEHAVIOR BY DEVELOPING ORGANIZATIONAL CULTURE THROUGH WORK ENGAGEMENT - Gunawan, Yuke Yolan; Anindita, Rina; Gunawan, Weka (UI Scholars Hub, 2023)
In the hospital industry, patient- and family-centered care is a key factor that measures hospital management performance. Hospital management requires the support of quality resources, especially human resources, who directly provide services to their customers. Therefore, Organizational Citizenship Behavior (OCB), known as extra role behavior from employees, is highly effective to apply because it can lead employees to deliver performance that goes beyond just performing their formal duties. The purpose of this study was to analyze the effect of organizational culture and leadership style on the OCB of employees in A Class A- Noncommunicable disease hospital in Jakarta through Work Engagement. The research method used a quantitative method with a sample of 260 employees. The hypotheses were tested through the SEM (Structural Equation Model) method with the SmartPLS3.0 application and SPSS version 27. The results showed that organizational culture, leadership style and work engagement affected OCB simultaneously. Organizational culture and leadership style were positively related to work engagement and OCB among employees. Meanwhile, leadership style affected OCB through work engagement. Having employees who demonstrate OCB is crucial to the hospitals to provide quality service delivery. Hence, maintain the stability of a positive organizational culture are required to improve work engagement amongst employee such as employee career development strategies and holding togetherness events that may increase work engagement thereby motivating employees to carry out OCB.